Desalination utilizing data centre waste heat - Wyon,Annie (2025)
This thesis approaches the challenges of data centre resource efficiency and global water scarcity through a techno-economic analysis of a desalination system driven by data centre waste heat. Membrane distillation is selected as a high-potential technology for this application and is examined through a case study of a hypothetical 1.5 MW direct-to-chip data centre located in Barcelona, Spain. Three use cases are defined for the water produced: input into data centre air-cooling, use in an electrolyser for hydrogen production as backup fuel for a data centre, and sale to the local water grid. Thermodynamic modelling was conducted in Python and included the direct contact membrane distillation modules based on literature, a commercial heat exchanger and two commercial pumps. Economic modelling was conducted to estimate the simplified cost of water per cubic meter produced together with an estimation of the space requirement. The results suggest that the system is technically feasible but faces economic challenges. This is largely due to high costs associated with pump investment and operation in relation to the low water production achieved by the low waste heat temperatures from the data centre. The data centre and electrolyser use cases show high potential, while sale to the water grid appears unsuitable due to high estimated cost in comparison to the local water price. Factors such as water availability in Spain and public opposition to data centre water use may influence the perceived economic feasibility and potentially improve the outlook for practical implementation of the system.
Keywords: Data centre waste heat; desalination; membrane distillation; direct-to-chip; Barcelona; Spain